1988
DOI: 10.1007/bf00687795
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and pathogenetic changes in the central nervous system of guinea pigs given tunicamycin

Abstract: Guinea pigs were injected with tunicamycin and the sequential morphological alterations in the brain examined to investigate further the pathogenesis of cerebral lesions in this experimental model of annual ryegrass toxicity, a central nervous system disease of livestock caused by members of the tunicamycin group of antibiotics. Brain damage was most commonly observed in the cerebellum, and the important alterations in the development of degenerative parenchymal lesions appeared to be largely referrable to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…3). These morphological changes are very similar to those described in mice and other species following tunicamycin injection (9,18,19).…”
Section: Ho Mice Exhibit Ablated Hepatic and Renal Injury Aftersupporting
confidence: 85%
“…3). These morphological changes are very similar to those described in mice and other species following tunicamycin injection (9,18,19).…”
Section: Ho Mice Exhibit Ablated Hepatic and Renal Injury Aftersupporting
confidence: 85%
“…The peak of weight loss also corresponded to an increase in blood urea nitrogen (BUN) and creatinine (a reflection of renal impairment), although these parameters proved more variable between animals than the weight loss and kidney histology (see below). These clinical phenomena are similar to those described in other species following tunicamycin injection (Koj et al 1986;Finnie andO'Shea 1988, 1989). Frozen sections of tunicamycin-treated kidneys from wild-type mice were immunostained for CHOP protein.…”
Section: Tunicamycin-treated Chop −/− Mice Have Decreased Programmed supporting
confidence: 79%
“…However, it has been reported that the disease is associated with missense mutations in some patients with long QT syndrome, leading to alteration of N-glycosylation sites required for the surfacemembrane localization of the HERG protein (16,17). In vivo studies have also showed that tunicamycin alters the expression of small intestinal brush border membrane glycoproteins (18) or increases the vascular permeability of the endothelial cells of central nervous system (19). Because tunicamycin is a naturally occurring antibiotic produced by some fungi, e.g., Streptomyces (20), or bacteria, e.g., Bacillus cereus (21), it would be interesting to learn whether glycosylation inhibitors secreted by such microorganisms could be involved in the pathogenesis of some acquired glomerular diseases.…”
Section: Discussionmentioning
confidence: 99%